2006
DOI: 10.3168/jds.s0022-0302(06)72356-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pure Holsteins Versus Crossbreds of Holstein with Normande, Montbeliarde, and Scandinavian Red

Abstract: Pure Holsteins (n = 380) were compared to Normande/Holstein crossbreds (n = 245), Montbeliarde/Holstein crossbreds (n = 494), and Scandinavian Red/Holstein crossbreds (n = 328) for 305-d milk, fat, and protein production during first lactation. Scandinavian Red was a mixture of Swedish Red and Norwegian Red. Cows were housed at 7 commercial dairies in California and calved from June 2002 to January 2005. All Holstein sires and all Holstein maternal grandsires were required to have a code assigned by the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
64
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 16 publications
13
64
2
5
Order By: Relevance
“…To evaluate fertility, survival and production, Holstein heifers and cows at the St. Paul and Morris dairies were bred to Jersey AI bulls. First-service conception rates between the Holsteins (41%) and Jersey × Holstein crossbreds (39%) were not different (Heins et al, 2008 (Heins et al, 2006b;Heins and Hansen, 2012), which have typically reported 2 to 3 weeks fewer days open of crossbreds v. Holsteins. Survival from first to second calving did not differ significantly for Jersey × Holstein crossbreds (80%) and Holsteins (71%) cows.…”
Section: Research Findings In the United Statesmentioning
confidence: 91%
See 1 more Smart Citation
“…To evaluate fertility, survival and production, Holstein heifers and cows at the St. Paul and Morris dairies were bred to Jersey AI bulls. First-service conception rates between the Holsteins (41%) and Jersey × Holstein crossbreds (39%) were not different (Heins et al, 2008 (Heins et al, 2006b;Heins and Hansen, 2012), which have typically reported 2 to 3 weeks fewer days open of crossbreds v. Holsteins. Survival from first to second calving did not differ significantly for Jersey × Holstein crossbreds (80%) and Holsteins (71%) cows.…”
Section: Research Findings In the United Statesmentioning
confidence: 91%
“…The decline in fertility and survival of Holstein led the managers of seven large dairies in California to mate Holstein heifers and cows with semen of the Normande and Montbeliarde breeds, as well as the Swedish Red and Norwegian Red. Crossbred cows calved for the first (Heins et al 2006a(Heins et al , 2006b(Heins et al and 2006c. Cows were followed up throughout their lifetimes to compare fertility, survival and profitabilty.…”
Section: Research Findings In the United Statesmentioning
confidence: 99%
“…Studies show that breeding for production has led to a reduction in secondary traits, especially those related to female fertility (e.g. Lucy, 2001;Heins et al, 2006aHeins et al, , 2006b). Thus, interest in crossbreeding Holstein cows to other breeds has increased; mainly to improve secondary traits, especially those related to female fertility (Weigel and Barlass, 2003;Funk, 2006;Buckley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, interest in crossbreeding Holstein cows to other breeds has increased; mainly to improve secondary traits, especially those related to female fertility (Weigel and Barlass, 2003;Funk, 2006;Buckley et al, 2014). Results of several studies have been reported including progeny of crosses between Holsteins and Normande, Montbéliarde, Scandinavian Red, Jersey and Brown Swiss (Dechow et al, 2007;Heins et al, 2006aHeins et al, , 2006bHeins et al, , 2006cMalchiodi et al, 2014;Olson et al, 2011). Generally these studies have demonstrated that purebred Holsteins are superior for milk production, but somewhat inferior for fertility and cow survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation